Reflection on teaching practice: Chilean university professor's training route - Padilla, Claudia; Madueño, María (Revista Innova Educación, 2019)
The purpose of this study was to understand how reflection on practice contributes to the teacher training of Chilean university professors. The research was a qualitative type based on the narrative method, and the technique applied was the semi-structured interview. 30 professors from two universities in Chile were interviewed. The main results lead to clarify that the reflection on the teaching practice represents a favorable route for the teacher's training. In particular, three critical aspects that from the voice of the participants contribute to teacher training are recognized: reflections on teaching practice; reflection from dialogue with peers and experts; and reflection on the practice that emerges from the interaction with the students themselves. In conclusion, it can be stand out that the reason why the reflection of the practice takes on meaning is because of the need to improve and solve everyday situations of the teaching task. Finally, Schön's position on reflection on practice is proposed as a transversal route of teacher training programs.
Keywords: Reflection; teacher training; Professors; Universities